Age of infection in epidemiology models - Fred Brauer (Electronic Journal of Differential Equations, 2005)
Disease transmission models in which infectivity depends on the time since infection are of importance in studying such diseases as HIV/AIDS. They also provide a means of unifying models with exposed stages or temporary immunity. We formulate a general age of infection model and carry out a partial analysis. There are open questions in the analysis of the characteristic equation at an endemic equilibrium.